Emotional coping implemented by teachers in Costa Rica for stress management - Retana-Alvarado, Diego Armando (2021)
Emotional coping implemented by teachers in Costa Rica for stress management” Teaching is one of the professions with the highest incidence of stress that affects not only the working life of professionals, but also transcends the personal sphere. There are few studies about emotional copy of primary education teachers in Costa Rica. The objective is to analyze emotional coping, implemented by educators working in the central canton of Alajuela (Costa Rica) in 2021. A survey online, adapted from the ED-6 (Teacher Stress Scale) instrument, was sent to 131 public school educators. The scale is made up of six dimensions: anxiety, depression, maladaptive beliefs, pressures, desmotivation and poor coping. Symptoms such as worry, insomnia, sweating, disturbance, anxiety, and tension suggest that teachers experience high levels of stress and are prone to developing depression, which is accompanied by excessive crying and sadness, lack of energy, and social changes. Although teachers are aware of the stressful elements to which they are exposed due to the nature of their profession and show emotional coping skills in the workplace, they reflect deficiencies with respect to the personal sphere.